A comprehensive review on characterization and modeling of thick capillary transition zones in carbonate reservoirs. (December 2016) - Bera, Achinta; Belhaj, Hadi
Graphical abstract: Abstract: Tight carbonate reservoirs exhibiting thick transition zones usually contain a large quantity of oil. Therefore, significant reserves might be left after secondary recovery by waterflooding not only due to the being in transition zones but also more due to the rock quality, tightness, pore throat and geometry, mineralogy, and wettability etc. Proper characterization and modeling of oil reservoirs are the key factors to predict their production performances, improve oil recovery and optimize the reservoir management. The development of saturation functions for transition zones, especially, of carbonate reservoirs is vital and challenging to address the multiphase flow and initial water saturation distribution in both static and dynamic modes. In this paper, a complete overview of the available experimental, modeling and simulation research works on transition zones in carbonate reservoirs is presented systematically. It is necessary to obtain a review of the past and present works so that the future researchers will get a clear idea of the approach on characterization and modeling of transition zones in carbonate reservoirs. Initial water saturation, hysteresis behaviors of relative permeability and capillary pressure, wettability alteration modeling and reserve estimation has been discussed in this paper. Petrographic and diagenesis study has also been discussed with the help of a few laboratory works from our research group. It is expected that this review will open new doors to the forthcoming researchers in this field. New thoughts and future works on transition zone characterization and modeling are also provided in this review as future developments and challenges.